ANALISIS BIAYA UNTUK PEMILIHAN SUMBER DAYA LISTRIK UTAMA RUMAH POMPA GREGES - Yudiono Yudiono; Umboro Lasminto; Vita Ratnasari (Journal of Civil Engineering, 2018)
The central government through the Directorate of Environmental Sanitation Development (PPLP) of theDirectorate General of Human Settlements of the Ministry of Public Works and Public Housing participated in theimplementation of drainage of Surabaya by providing assistance for the construction of Greges pump house. The pump houseGreges as one of the pump house located in Surabaya, is one of the drainage system controllers around BozemMorokrembangan area especially the flow of water along the Greges channel which is also an outlet for several channels. Inthe aid of the pump house choose to use Genset as the main power source (SDL). While the Government of Surabaya alwayswants the use of SDL from PLN. The purpose of this study was to analyze the use of SDL to meet the needs of the GregesPump House by performing the cost analysis required for the Greges pump house for the use of Genset and PLN powersources, and determining the better SDL selection that would be used to meet the needs of the Greges pump house. Based onthe analysis of costs, the use of generators is better than PLN in the investment cost analysis. Based on PLN operational costanalysis is better than generator. In the first year period the total cost for the use of PLN is Rp. 5.102.223.905 greater thanthe generator Rp. 4.789.084.970,16,, in the second year the cost of using PLN approaches the generator cost, and on the thirdand so the use of generator is higher than the PLN.